Quantum effects in silicon isotopes at low temperatures under normal and high pressures. (8th December 2017) - Enkovich, P V; Brazhkin, V V; Lyapin, S G; Novikov, A P; Gusev, A V; Gavva, V A; Churbanov, M F; Stishov, S M
Abstract: Precision studies of Raman scattering in isotopically pure 28 Si, 29 Si, and 30 Si single crystals have been performed in the temperature range from 8 to 300 K. It was found that the quantum effects manifest themselves noticeably at low temperatures ( T  ≤ 100 K). This can be seen from the difference ∼(0.4 ± 0.1) cm −1 between the normalized frequencies of two extreme 28 Si and 30 Si isotopes, while at room temperature, quantum effects are not visible and are comparable with the measurement error of frequencies (0.1 cm −1 ). Raman scattering in silicon isotopes in the region of noticeable quantum effects has been studied under hydrostatic conditions at pressures to 12 GPa and at a temperature of Т  = 80 K. Quantum effects are not changed under compression within the accuracy of measurements.